FAKTOR YANG MEMPENGARUHI PROSES PENGAMBILAN KEPUTUSAN WISATAWAN BERKUNJUNG KE OBJEK WISATA RELIGI MASJID AGUNG ISLAMIC CENTRE KABUPATEN ROKAN HULU - Dina Amalina; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research purposed to get know about the factor that influence the decision-making process of tourists visiting the religious object of the Masjid Agung Islamic Centre of Rokan Hulu Regency and know about the most dominant factors of the decision making process of tourists visiting. This research uses quantitative descriptive method to analize the problems. The sample in this research is the tourists who visited the religious object of the Masjid Agung Islamic Centre of Rokan Hulu Regency. The Sample of this research is 100 people taken by accidental sampling technique. Data collected in this research are observation, questionnaire and documentation. And use the Linkert Scale to find out the length of the Interval. As a result of the research, the tourists in Masjid Agung Islamic Centre said they were agreed about the factors of decision making influenced their decision to visit the religious object of the Masjid Agung Islamic Centre Rokan Hulu Regency and the awareness benefits of travel is a very determining factor in the proces of decision making to visit.Keywords: decision making factor, tourist, religious tourism object